2018
DOI: 10.1016/j.ajhg.2018.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Missense Variants in HIF1A and LACC1 Contribute to Leprosy Risk in Han Chinese

Abstract: Genome-wide association studies (GWASs) and genome-wide linkage studies (GWLSs) have identified numerous risk genes affecting the susceptibility to leprosy. However, most of the reported GWAS hits are noncoding variants and account for only part of the estimated heritability for this disease. In order to identify additional risk genes and map the potentially functional variants within the GWAS loci, we performed a three-stage study combining whole-exome sequencing (WES; discovery stage), targeted next-generati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(62 citation statements)
references
References 79 publications
1
57
1
Order By: Relevance
“…This finding suggested a role for synapsin-2 in the progression of infection from mycobacteria to the nerves (117). Unexpectedly, two oxidative stress-related genes, SOD2 and HIF1A, were also found to be associated with leprosy, which may be explained by the possibility that oxidative stress is a means of defense used by M. leprae-infected cells (158,159). Early in 2004, a genome-wide linkage scan study reported the association between the 5 ′ regulatory region of PARK2/PACRG and Vietnamese leprosy, which was confirmed in Brazilian leprosy patients (160).…”
Section: Other Leprosy-associated Genesmentioning
confidence: 94%
“…This finding suggested a role for synapsin-2 in the progression of infection from mycobacteria to the nerves (117). Unexpectedly, two oxidative stress-related genes, SOD2 and HIF1A, were also found to be associated with leprosy, which may be explained by the possibility that oxidative stress is a means of defense used by M. leprae-infected cells (158,159). Early in 2004, a genome-wide linkage scan study reported the association between the 5 ′ regulatory region of PARK2/PACRG and Vietnamese leprosy, which was confirmed in Brazilian leprosy patients (160).…”
Section: Other Leprosy-associated Genesmentioning
confidence: 94%
“…In addition, we took advantage of the exome sequencing data of 107 genetically unrelated AD patients (authors' unpublished data) that were selected using an extreme phenotype sampling strategy [51], to identify potential disease-causal/rare/functional variants in the exonic regions of the COX-related genes by comparing to 368 control subjects (including 160 in-house nondementia controls [52], Han Chinese in Beijing (CHB, N = 103) and Southern Han Chinese (CHS, N = 105) from the 1000 Genomes Project phase 3 [53,54]). These genetically unrelated AD patients (46.7% females, age 64.6 ± 10.29 years, 37.4% were APOE ε4 carriers) either had an early onset age <= 55 years old and/ or a positive family history (presence of disease in one or more first-degree family members).…”
Section: Subjectsmentioning
confidence: 99%
“…For sequencing the exon and flanking regions of the COX-related genes, we used the next generation sequencing technologies as described in our previous studies [47,52,60]. In brief, the paired-end reads were generated on the HiSeq 4000 sequencer (Illumina).…”
Section: Subjectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, LRRK2 is a negative regulator of inflammasome activation ( 56 , 57 ) and an inducer of ROS production ( 54 , 57 ), two known mechanisms of immune defense against bacterial infections also modified by variants of LACC1 , a gene consistently associated with leprosy ( 20 , 25 , 34 , 35 ). Recently, the LACC1 contribution to leprosy risk has been reinforced: a GWAS-based analysis focusing on functional variants detected association between leprosy and a LACC1 missense variant (rs3764147, c.760A > G, p.Ile254Val) ( 22 ).…”
Section: Introductionmentioning
confidence: 99%